Anti-malarial drugs and the prevention of malaria in the population of malaria endemic areas - Greenwood Brian (Malaria Journal, 2010)
Abstract Anti-malarial drugs can make a significant contribution to the control of malaria in endemic areas when used for prevention as well as for treatment. Chemoprophylaxis is effective in preventing deaths and morbidity from malaria, but it is difficult to sustain for prolonged periods, may interfere with the development of naturally acquired immunity and will facilitate the emergence and spread of drug resistant strains if applied to a whole community. However, chemoprophylaxis targeted to groups at high risk, such as pregnant women, or to periods of the year when the risk from malaria is greatest, can be an effective and cost effective malaria control tool and has fewer drawbacks. Intermittent preventive treatment, which involves administration of anti-malarials at fixed time points, usually when a subject is already in contact with the health services, for example attendance at an antenatal or vaccination clinic, is less demanding of resources than chemoprophylaxis and is now recommended for the prevention of malaria in pregnant women and infants resident in areas with medium or high levels of malaria transmission. Intermittent preventive treatment in older children, probably equivalent to targeted chemoprophylaxis, is also highly effective but requires the establishment of a specific delivery system. Recent studies have shown that community volunteers can effectively fill this role. Mass drug administration probably has little role to play in control of mortality and morbidity from malaria but may have an important role in the final stages of an elimination campaign.